Introduction to Literature Fairy Tales, Folk Tales, and How They Shape Us - Young, Judy (Open textbook library., 2024)
Introduction to Literature: Fairy Tales, Folk Tales, and How They Shape Us introduces college freshmen to the study of literature through a focus on texts that, generally, they already know, or think they know, and how those texts aim to shape audiences to be compliant cultural objects. The book is organized around several prominent story groups, including various genres and forms, meant to promote discussion and discovery leading to students’ understanding that these texts function as cultural sculptors of readers’ principles and behaviors. Students develop the skill of analyzing texts and creating sound arguments about them through class discussions and a series of writing assignments. Ideally, they leave the course understanding how to create a sound argument and, more pointedly, that there is no such thing as “just a story.”